1981
DOI: 10.1007/bf02377120
|View full text |Cite
|
Sign up to set email alerts
|

Proteoid root morphology and function inLupinus albus

Abstract: SummaryCurrent theories of phosphorus uptake by plants imply that they can augment diffusion to their root axes by the development of abundant root hairs or mycorrhizas. Some phosphorus efficient plants have root morphology with multi-branched roots and localised regions of densely packed root hairs, which we suggest is better suited to the retention of substances exuded by the roots than uptake of substances moving to the root by diffusion. Evidence of substantial exudation by the proteoid roots of Lupinus al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
82
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 10 publications
2
82
0
1
Order By: Relevance
“…Phosphate uptake has been shown to be more efficient in proteoid than non-proteoid roots (Jeffrey, 1967;Lamont 1982;Vorster & Jooste 1986 a, b). The large surface area increases the secretion of phosphatesolubilizing compounds into localized regions of the rhizosphere (Gardner et al, 1981(Gardner et al, , 1982a. This is important in the natural environment where phosphorus acquisition is most likely to be limited by the low solubility and diffusion of phosphorus across the soil to the root absorbing surfaces.…”
Section: N T R O D Ii C Tionmentioning
confidence: 99%
“…Phosphate uptake has been shown to be more efficient in proteoid than non-proteoid roots (Jeffrey, 1967;Lamont 1982;Vorster & Jooste 1986 a, b). The large surface area increases the secretion of phosphatesolubilizing compounds into localized regions of the rhizosphere (Gardner et al, 1981(Gardner et al, , 1982a. This is important in the natural environment where phosphorus acquisition is most likely to be limited by the low solubility and diffusion of phosphorus across the soil to the root absorbing surfaces.…”
Section: N T R O D Ii C Tionmentioning
confidence: 99%
“…Bado (2002) and Husson et al (2010) indicated that in monoculture, cowpea can fix between 50 and 115 kg of nitrogen per hectare. Cowpea also improves soil physical and biological properties and makes calcium phosphates and phosphorous soluble with the help of root exudation (Hoshikawa, 1990;Gardner et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 And this electrochemical gradient plays an important role both in P-deficiency and Al-induced citrate exudation from plant roots. For examples, Gardner et al [26][27][28] provided the first evidence that organic acid exudation from specialized proteoid roots (dense bottle-brushlike clusters of rootlets) of white lupin (Lupinus albus) to enhance P uptake by molubilization of poorly available soil P. Since then, there has been increased interest worldwide in the role of the plasma membrane H C -ATPase in the regulation of organic acids exudation from plant roots. In white lupin, Yan et al 12 reported that P deficiency induced higher plasma membrane H C -ATPase activity and its concentration in active proteoid roots than in other roots.…”
mentioning
confidence: 99%